Presence of Autoimmune Antibody in Chikungunya Infection - Wirach Maek-a-nantawat; Udomsak Silachamroon (Case Reports in Medicine)
Chikungunya infection has recently re-emerged as an important arthropod-borne disease in Thailand. Recently, Southern Thailand was identified as a potentially endemic area for the chikungunya virus. Here, we report a case of severe musculoskeletal complication, presenting with muscle weakness and swelling of the limbs. During the investigation to exclude autoimmune muscular inflammation, high titers of antinuclear antibody were detected. This is the report of autoimmunity detection associated with an arbovirus infection. The symptoms can mimic autoimmune polymyositis disease, and the condition requires close monitoring before deciding to embark upon prolonged specific treatment with immunomodulators.